KLF7-transfected Schwann cell graft transplantation promotes sciatic nerve regeneration. (6th January 2017) - Wang, Ying; Li, Wen-yuan; Jia, Hua; Zhai, Feng-guo; Qu, Wen-rui; Cheng, Yong-xia; Liu, Yan-cui; Deng, Ling-Xiao; Guo, Su-fen; Jin, Zai-shun
Graphical abstract: Highlights: AAV2-KLF7 efficiently transduced KLF7 to SCs. KLF7-SCs promote Schwann cells proliferation and neurites outgrowth of DRG explants. The expression of KLF7 target genes were enhanced in SCs overexpressing KLF7. KLF7-SCs enhance motor and sensory axonal regeneration which resulted in motor functional recovery. Abstract: Our former study demonstrated that Krüppel-like Factor 7 (KLF7) is a transcription factor that stimulates axonal regeneration after peripheral nerve injury. Currently, we used a gene therapy approach to overexpress KLF7 in Schwann cells (SCs) and assessed whether KLF7-transfected SCs graft could promote sciatic nerve regeneration. SCs were transfected by adeno-associated virus 2 (AAV2)-KLF7 in vitro . Mice were allografted by an acellular nerve (ANA) with either an injection of DMEM (ANA group), SCs (ANA + SCs group) or AAV2-KLF7-transfected SCs (ANA + KLF7-SCs group) to assess repair of a sciatic nerve gap. The results indicate that KLF7 overexpression promoted the proliferation of both transfected SCs and native SCs. The neurite length of the dorsal root ganglia (DRG) explants was enhanced. Several beneficial effects were detected in the ANA + KLF7-SCs group including an increase in the compound action potential amplitude, sciatic function index score, enhanced expression of PKH26-labeling transplant SCs, peripheral myelin protein 0, neurofilaments, S-100, and myelinated regeneration nerve. Additionally, HRP-labeled motoneurons in the spinal cord, CTB-labeled sensory neurons in the DRG, motor endplate density and the weight ratios of target muscles were increased by the treatment while thermal hyperalgesia was diminished. Finally, expression of KLF7, NGF, GAP43, TrkA and TrkB were enhanced in the grafted SCs, which may indicate that several signal pathways may be involved in conferring the beneficial effects from KLF7 overexpression. We concluded that KLF7-overexpressing SCs promoted axonal regeneration of the peripheral nerve and enhanced myelination, which collectively proved KLF-SCs as a novel therapeutic strategy for injured nerves.